2016
DOI: 10.1007/s13187-016-1154-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Methods Verifying Volunteers’ Ability to Provide Hospice Care

Abstract: The subject of the presented work was an attempt at optimization of the methods used for verification of the candidates for medical voluntary workers in a hospice and decreasing the danger of a negative influence of an incompetent volunteer on a person in a terminal stage of a disease and his or her relatives. The study was carried out in St. Lazarus Hospice in Krakow, Poland, and included 154 adult participants in four consecutive editions of “A course for volunteers – a guardian of the sick” organized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…By contrast, people recently bereaved, overly zealous in their religious views, overly wordy, or lacking social support are discouraged from becoming involved in delivering EoLC (Claxton-Oldfield & Banzen, 2010). Despite those accumulated findings, reviews have also shown that no standardized criteria for EoLC volunteer screening have been developed nor has any instrument to effectively select applicants with qualities desired for providing EoLC (Pesut et al, 2014; Szeliga & Mirecka, 2018).…”
Section: Gap 1: Difficulties In Recruiting and Selecting Suitable Volmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, people recently bereaved, overly zealous in their religious views, overly wordy, or lacking social support are discouraged from becoming involved in delivering EoLC (Claxton-Oldfield & Banzen, 2010). Despite those accumulated findings, reviews have also shown that no standardized criteria for EoLC volunteer screening have been developed nor has any instrument to effectively select applicants with qualities desired for providing EoLC (Pesut et al, 2014; Szeliga & Mirecka, 2018).…”
Section: Gap 1: Difficulties In Recruiting and Selecting Suitable Volmentioning
confidence: 99%
“…For those reasons, volunteers in providing EoLC should have clear communication skills involving active empathetic listening (Worthington, 2008) and a heightened awareness of setting reasonable boundaries between patients and volunteers and taking good care of themselves during service (Claxton-Oldfield et al, 2011; Soderhamn et al, 2017). However, despite the range of programs for volunteers in EoLC implemented in hospices/hospitals (e.g., Szeliga & Mirecka, 2018), little consensus has been achieved on the context-specific capacities required by volunteers in delivering EoLC in community settings, and even less is known about how to best train selected individuals to effectively provide community-based EoLC services (S. M. Morris et al, 2017).…”
Section: Gap 2: Need Context-specific Capacity For Eolc Volunteers Inmentioning
confidence: 99%